PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN GEOGEBRA TERHADAP HASIL BELAJAR MATERI PRISMA DI SMP - Khairah, Ummy; R, Zubaidah; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aim to knowing and describe the results of students learning who take learning problem based learning model through geogebra media with who follow problem based learning model through whiteboard in the material surfice area and volume prism as well as to the contribution of media use geogebra on towards student’s study results in the material surfice area and volume prism. The form of this research was a quasy experimental design with nonequivalent control group design. The sample of this research are VIII B as experiment class and VIII C as control class. The average learning outcomes of students in experiment class is 12,79, while the average learning outcomes of students in control class is 11,24. Based on the U Mann-Whitney test with significance 0,05 indicated there were differences between problem based learning model through geogebra media with who follow problem based learning model through whiteboard in the material surfice area and volume prism. The value of effect size is 0,52 with moderate category. This suggests that the role of media GeoGebra considerable influence on towards studenst’s study results in prism material.Keywords: Problem Based Learning, GeoGebra Media, Student’s Study Results